The Impacts of Consumptive Behaviors toward American Society in Modern Era as Reflected in the Film The Joneses - Ambarwati Budi Rahayu; Nadella Lesmana; Didik Murwantono (Universitas Cokroaminoto Palopo, 2020)
In this research, the writers make research of consumptive behavior and its impacts. “The Joneses” film represents the impacts of consumptive behavior in American society in many aspects of life. The objective of this paper is to describe and find the impacts of consumptive behavior toward American society, as reflected in the film